2000
DOI: 10.1089/10430340050129503
|View full text |Cite
|
Sign up to set email alerts
|

Gene Electrotransfer Results in a High-Level Transduction of Rat Skeletal Muscle and Corrects Anemia of Renal Failure

Abstract: We have investigated the efficacy of a gene transfer strategy based on plasmid DNA electroinjection for the correction of anemia associated with renal failure. An expression plasmid encoding the rat erythropoietin (EPO) cDNA under the control of the CMV promoter as constructed and utilized for this work. Electroinjection of pCMV/rEPO in different rat muscles yielded sustained and long-term EPO production and secretion. The muscle-produced EPO corrected the anemia in five of six nephrectomized rats, used as a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
71
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(75 citation statements)
references
References 43 publications
4
71
0
Order By: Relevance
“…19 The efficiency of gene transfer by electroporation is greater by several orders of magnitude than that of passive DNA transfer (see Fig 1). Electrotransfer of the endostatin gene into normal tissues ( muscle ) could also be achieved (Fig 4) and several previous studies have indicated that electrotransfer into muscle of other therapeutic genes such as those encoding interleukin -12 (e.g., Hanna et al 34 ) and erythropoietin ( e.g., Rizzuto et al 35 ) or FGF 1 ( e.g., Mir et al 36 ) is very effective. Transfer of the endostatin gene into muscles resulted in augmented levels of circulating endostatin ( Fig 4) and diminished the number of metastatic foci in mouse lungs ( Fig 5) ( see also Blezinger et al 17 ).…”
Section: Discussionmentioning
confidence: 86%
“…19 The efficiency of gene transfer by electroporation is greater by several orders of magnitude than that of passive DNA transfer (see Fig 1). Electrotransfer of the endostatin gene into normal tissues ( muscle ) could also be achieved (Fig 4) and several previous studies have indicated that electrotransfer into muscle of other therapeutic genes such as those encoding interleukin -12 (e.g., Hanna et al 34 ) and erythropoietin ( e.g., Rizzuto et al 35 ) or FGF 1 ( e.g., Mir et al 36 ) is very effective. Transfer of the endostatin gene into muscles resulted in augmented levels of circulating endostatin ( Fig 4) and diminished the number of metastatic foci in mouse lungs ( Fig 5) ( see also Blezinger et al 17 ).…”
Section: Discussionmentioning
confidence: 86%
“…This concern has recently been addressed by the development of in vivo electrotransfer techniques that have routinely achieved a 10-to 100-fold increase in expression. [8][9][10]15 The LacZ reporter gene was used in present studies, as its expression is easily quantifiable by histochemistry and ELISA thus allowing an assessment of both the number of positive fibres and the overall levels of expression. Samples were taken at 5 days after injection, as this represents the peak of ␤-galactosidase expression in these animals following direct injection alone.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports of high efficiency electrotransfer have also noted the association of muscle damage with efficient gene transfer. 10 Other studies, however, have failed to comment on the muscle histology 9,15 although in some cases the figures showed evidence of muscle damage. 8 Hyaluronidase has previously been used to improve the efficiency of virus-based in vivo gene transfer methods.…”
Section: Figure 4 Total Level Of Expression Of ␤-Galactosidase In Musmentioning
confidence: 99%
See 1 more Smart Citation
“…The signal intensity is determined experimentally in water from a phantom with calibrated concentrations of Gd-DOTA, in acquisition conditions identical to those used in vivo. From the measurements obtained in the water phantom and from muscle relaxation times, the equation linking the signal increase R ¼ (SiÀSm)/Sm to the concentration of Gd-DOTA C is C ¼ 0:099R þ 0:154R 2 We here assume that So is not modified, and that the influence of T2 variation can be neglected since TE value is short. This is an acceptable approximation at value of electric field under 200 V/cm where T2 and T1 variations induced by oedema are weak.…”
Section: Appendix I: Quantification Of the Ca Trapped Quantitymentioning
confidence: 99%